1976
DOI: 10.1902/jop.1976.47.11.643
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Periodontal Disease in Sheep

Abstract: A histological investigation was carried out of the periodontia of young and mature sheep obtained from areas where a periodontal syndrome is endemic in sheep flocks. Observations of the incisor periodontia, which are most commonly affected by the syndrome, revealed no evidence of degenerative or pathological changes of alveolar bone, periodontal ligament or cementum compared with the periodontia of control animals. Minor inflammatory changes of the gingivae, associated with small amounts of a filamentous-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…The connective tissue behind it is infiltrated by plasma cells. At the base of the pocket, the junctional epithelium is very short and connective tissue is infiltrated by neutrophils migrating to the apical plaque border , then forming an interface layer [108]. The inflammation of the gingiva appears to be moderate.…”
Section: The Different Animal Models In Periodontologymentioning
confidence: 99%
“…The connective tissue behind it is infiltrated by plasma cells. At the base of the pocket, the junctional epithelium is very short and connective tissue is infiltrated by neutrophils migrating to the apical plaque border , then forming an interface layer [108]. The inflammation of the gingiva appears to be moderate.…”
Section: The Different Animal Models In Periodontologymentioning
confidence: 99%
“…Listgarten et al 1978, Reichart et ai. 1979, marmosets (Levy 1976), and dogs (Schroeder & Lindhe 1980), but not in sheep (Cutress 1976). In principle, there are three forms of resorption: surface, inflammatory, and replacement.…”
Section: The Clinical Radiographic and Histopathologic Observationsmentioning
confidence: 99%
“…Accumulation of plaque and calculus invariably led to the development of inflammatory changes in the periodontal complex. Compared to the great number of experimental periodontitis studies, few examinations are available on ora] health and periodontal status in domestic animals which have not undergone specific treatment (Bell 1966, Cutress 1976. A comprehensive review of the pathogenesis of inflammatory periodontal disease in man and animal was published (Page & Schroeder 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Factors which have been suggested include excessive stress on incisors (Hitchin & Walker-Love 1959;Benzie & Cresswell 1962;Markham & Lyle-Stewart 1962;Duckworth et al 1962); insufficient dental exercise (Porter et al 1970); genetic effects (Hitchin 1948); selenium deficiency (Cutress & Ludwig 1969); low calcium and phosphorus intake (Gunn 1969); low serum calcium and albumin levels (Cutress et al 1972;Suckling et al 1974); and localised bacterial activity on the tooth surface (Cutress 1976). In a review of the literature of periodontal disease, Cutress & Ludwig (1969) concluded that although genetic factors could not be considered as the basic cause of periodontal disease, they could not be ruled out as predisposing factors.…”
Section: Introductionmentioning
confidence: 99%